A Contrastive Analysis on Prefix Usage in Batak Toba and English: Morphological Perspectives - Heppy Theresia Sitompul; Rajamin Keposan Lingga (Prodi Sastra Inggris, Universitas Muhammadiyah Semarang, 2024)
This study aims to investigate and describe the differences in prefix usage in English and Batak Toba from a morphological perspective. This research employs a qualitative method with a descriptive approach. Data were taken from an English short story titled “The Mysterious Disappearance” and a Batak short story titled “Mandiori Pulungan”, both accessed from the internet. The findings indicate that there are significant differences in the use of prefixes between English and Batak Toba, both in form and meaning. Each language has a unique prefix system that affects word meaning differently. In conclusion, contrastive analysis reveals fundamental differences in prefix usage in these two languages.